Evolutionary psychological perspectives on filicide are applicable in modern-day Norway - Ottesen, Vibeke (Frontiers in Psychology, 2023)
Current evolutionary psychological (EP) perspectives on filicide perpetration propose that it is an extreme behavioural manifestation of psychological mechanisms that evolved due to their function towards enabling ancestrally adaptive discriminative parental investment. Predictions concerning the characteristics traits of filicide derived from this hypothesis have been empirically supported cross-culturally. Still, it remains a theoretical and empirical question whether EP perspectives on filicide are applicable in societies where the general population is alleviated from ancestrally salient cues to reproductive conflict between individuals and children in their care and the opportunities for lethal caretaker behaviours are highly constricted. Compiling a national sample of filicide cases in modern-day Norway, the present study catered for testing whether EP perspectives on filicide apply in such a society. As predicted, the majority of incidents (79,5%) were associated with perpetrator psychopathology (psychotic episode or filicide-suicide). This further catered for testing the EP hypothesis that filicides associated with perpetrator psychopathology will be characterized by traits that contradict an ancestrally adaptive logic for discriminant parental investment . A full series of predictions derived from this hypothesis was supported as filicides with this association included no step-parental perpetrators and, when compared against filicides that were not associated with perpetrator psychopathology, had older victims and perpetrators and more often multiple victims. The findings confirm the potential applicability of EP perspectives on filicide in progressive and highly developed welfare states, thus lending support to their universal validity.